Study Of Protein, Lipid And Metabolite Profiles In Type 2 Diabetes Mellitus (T2dm) Rats Model Upon High Calories Food Intake And Metformin Treatment - Sim, Xuan Yi (2021)
Type 2 diabetes mellitus (T2DM) is a metabolic disease characterized by high blood glucose due to insulin resistance or insulin deficiency. Type 2 diabetes is primarily caused by an unhealthy lifestyle. Lifestyle management such as healthy diet and physical activity is essential for diabetes management. Food prepared in oil or high fat content add taste and textures to the palate; therefore, it is more favourable by most people. In this study, metabolic parameters, proteins (kidney), lipids (blood), and metabolites (urine) profile of T2DM rats were studied upon palm oil enriched-high fat diet and metformin treatment.